Parasagittal Meningioma: A Comprehensive Case Series and Systematic Review - Aman, Renindra Ananda; Desbassarie, Fitrie; Purwodito, Arief; Syarif, Ricky Rusydi; Calvin, Nicholas; Paat, Bipatra Einstein Yacobus (Jurnal Medis Islam Internasional, 2024)
Introduction: This case series included seven patients diagnosed with parasagittal meningioma, presenting their clinical histories, management, and outcomes. In parallel, a systematic review synthesized the existing literature on parasagittal meningioma. This comprehensive analysis combined the findings from both the case series and the systematic review to provide a holistic understanding of these tumors. This case series included seven patients diagnosed with parasagittal meningioma, presenting their clinical histories, management, and outcomes. In parallel, a systematic review synthesized the existing literature on parasagittal meningioma. This comprehensive analysis combined findings from both the case series and the systematic review to provide a holistic understanding of these tumors. Results: This case series highlights the clinical heterogeneity of parasagittal meningiomas and presents cases with various clinical presentations, treatment approaches, and outcomes. The systematic review consolidates existing knowledge and reveals gaps in the understanding of optimal management for these tumors. The combination of case series and systematic reviews provides valuable insights into the clinical behavior, treatment strategies, and prognostic factors associated with parasagittal meningioma. Conclusions: Parasagittal meningioma presents unique diagnostic and therapeutic challenges. This comprehensive study offers a multifaceted perspective on these tumors, enhancing our understanding of their clinical characteristics and management options. These findings can guide clinicians in making informed decisions and improving patient outcomes in the field of neuro-oncology.